2022
DOI: 10.3389/fphar.2022.871583
|View full text |Cite
|
Sign up to set email alerts
|

p53/NF-kB Balance in SARS-CoV-2 Infection: From OMICs, Genomics and Pharmacogenomics Insights to Tailored Therapeutic Perspectives (COVIDomics)

Abstract: SARS-CoV-2 infection affects different organs and tissues, including the upper and lower airways, the lung, the gut, the olfactory system and the eye, which may represent one of the gates to the central nervous system. Key transcriptional factors, such as p53 and NF-kB and their reciprocal balance, are altered upon SARS-CoV-2 infection, as well as other key molecules such as the virus host cell entry mediator ACE2, member of the RAS-pathway. These changes are thought to play a central role in the impaired immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 172 publications
1
26
0
Order By: Relevance
“…Our results show that in saliva, p53 apoptosis effector is less abundant (FC −2.52) in patients with COVID-19, corroborating the results obtained by Cui et al, 2021, and suggested by Milani et al, 2022 [ 22 , 23 , 24 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that in saliva, p53 apoptosis effector is less abundant (FC −2.52) in patients with COVID-19, corroborating the results obtained by Cui et al, 2021, and suggested by Milani et al, 2022 [ 22 , 23 , 24 ].…”
Section: Resultssupporting
confidence: 92%
“…The physiological significance of p53 basal activity is still emerging, as p53 suppression is linked to the disruption of tissue hemostasis. Low basal levels of p53 have been associated with respiratory disorders, suggesting a protective role for p53 in vascular hemostasis and inflammation of the lungs [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dissecting the intricate features of complex phenotypes (Singh et al, 2010;Gemmati et al, 2012;Gemmati and Tisato, 2023), as COVID-19 and the vaccine-induced immune response in different individuals, is an intricate task, being the result of genome-phenome combinations, and a specific OMICs (COVIDomics) approach is the best way to face them (Gemmati et al, 2019;Gemmati et al, 2020;Gemmati and Tisato, 2020;Milani et al, 2022). During COVID-19 pandemic and anti-SARS-CoV-2 vaccination campaign, unpredictable Frontiers in Genetics frontiersin.org 13 extreme phenotypes (clinical and laboratory) have been observed, suggesting that inherited traits and predispositions at an individual or population level may account for such manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Host genetics and acquired factors modulate the clinical phenotypes of COVID-19 by complex interactions occurring between SARS-CoV-2 and human cells and represent issues investigated by the COVID-19 Host Genetics Initiative (HGI) ( Severe Covid et al, 2020 ; COVID-19 Host Genetics Initiative, 2021 ); moreover, host genetics may also give precious information on the strength of the individual vaccine immune response and efficacy ( Jonsson et al, 2017 ; Colucci et al, 2021 ; Castro Dopico and Karlsson Hedestam, 2022 ; Venkataraman et al, 2022 ). It is to be noted that the same panel of inherited and acquired factors or combinations of them seems to contribute to both COVID-19 progression and vaccine immune response by sharing common mechanisms and pathways ( Gemmati et al, 2020 ; Gemmati and Tisato, 2020 ; Tiwari Pandey et al, 2020 ; Zauli et al, 2020 ; Cuapio et al, 2022 ; Milani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also discovered that ACE2 is a functional host receptor for COVID-19 [ 81 , 82 ]. COVID-19 reduces the expression of p53 after entering the host cells, causing a homeostasis imbalance [ 83 ]. Our KEGG enrichment analysis revealed that the expression of differential genes in the p53 signaling pathway was similar among the genes altered in the same direction by PO and VO, providing a good reference for our treatment.…”
Section: Discussionmentioning
confidence: 99%